THE EFFECT OF FINANCIAL PERFORMANCE AND COMPANY SIZE ON STOCK PRICES WITH CORPORATE SOCIAL RESPONSIBILITY (CSR) AS A MODERATING VARIABLE IN COAL MINING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2017-2021 - Mustafa, Gading; Halim, Edyanus Herman; Haryetti, Haryetti (Program Pascasarjana, Universitas Riau, 2023)
This study examines the effect of financial performance and company size on stock prices with Corporate Social Responsibility (CSR) as a moderating variable. The population in this study consists of coal mining companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period, totaling 27 companies. Using quantitative and secondary data obtained from the IDX website and the companies' annual reports, the sample selection employed a purposive sampling method, resulting in 95 data points from 19 companies for each period. Data analysis was conducted using Structural Equation Modelling-Partial Least Square (SEM-PLS). The results showed that Return on Equity (ROE) positively and significantly affects stock prices, while Earnings per Share (EPS) negatively and significantly affects stock prices. Company size has a negative and insignificant effect on stock prices. CSR, as a moderating variable, is not able to moderate the positive relationship between ROE and stock price, but it can moderate the negative relationship between EPS and stock prices, as well as the negative relationship between company size and stock prices.